2021
DOI: 10.1038/s41467-021-26380-y
|View full text |Cite
|
Sign up to set email alerts
|

Generation of hydroxyl radical-activatable ratiometric near-infrared bimodal probes for early monitoring of tumor response to therapy

Abstract: Tumor response to radiotherapy or ferroptosis is closely related to hydroxyl radical (•OH) production. Noninvasive imaging of •OH fluctuation in tumors can allow early monitoring of response to therapy, but is challenging. Here, we report the optimization of a diene electrochromic material (1-Br-Et) as a •OH-responsive chromophore, and use it to develop a near-infrared ratiometric fluorescent and photoacoustic (FL/PA) bimodal probe for in vivo imaging of •OH. The probe displays a large FL ratio between 780 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 70 publications
0
40
0
Order By: Relevance
“…These results showed that R&HV‐Gd@ICG had drastically increased intracellular ROS generation upon X‐ray irradiation. Because more than 50% of the DNA damage in standard RT is due to •OH, [ 21 ] •OH generation was further confirmed using the commercial probe, hydroxyphenyl fluorescein (HPF), which can emit 515 nm green fluorescence after reacting with generated •OH. As shown in Figure S16 of the Supporting Information, the HPF fluorescence in R&HV‐Gd@ICG solution was significantly more intense than the deionized (DI) water under the same X‐ray irradiation ( p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…These results showed that R&HV‐Gd@ICG had drastically increased intracellular ROS generation upon X‐ray irradiation. Because more than 50% of the DNA damage in standard RT is due to •OH, [ 21 ] •OH generation was further confirmed using the commercial probe, hydroxyphenyl fluorescein (HPF), which can emit 515 nm green fluorescence after reacting with generated •OH. As shown in Figure S16 of the Supporting Information, the HPF fluorescence in R&HV‐Gd@ICG solution was significantly more intense than the deionized (DI) water under the same X‐ray irradiation ( p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, since people are not accustomed to using “turn‐off” fluorescence for disease diagnosis, “turn‐on” probes are more welcome and reported for bioimaging analyses. [ 16 ] Therefore, “turn‐on” fluorescence probes are competent for real‐time imaging of S. aureus infections, which have not yet been exploited.…”
Section: Introductionmentioning
confidence: 99%
“…Although near-infrared fluorescence (NIRF) imaging with the characteristics of noninvasion, high sensitivity, and real time has emerged to detect hNQO1 activity, its limited penetration depth and auto-fluorescent interference hamper longitudinal imaging in vivo. Intriguingly, photoacoustic (PA) imaging, especially ratiometric PA (RPA) imaging, which is a potent complement to NIRF imaging, enables deep tissue penetration and noninvasive visualization with collecting biological data from the entire tissue volume as well as provides built-in self-calibration for signal correction to make the detection with high sensitivity and reliability. Therefore, the integration of NIRF and RPA duplex imaging benefits accurate diagnosis of hNQO1 activity in vivo. …”
Section: Introductionmentioning
confidence: 99%